1988
DOI: 10.3171/jns.1988.68.6.0908
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal drainage of chronic subdural hematomas in older patients

Abstract: Most patients with chronic subdural hematoma are successfully treated with trephination and external drainage. However, hematomas with thick membranes may persist or recur, needing reoperation or major surgery such as craniotomy with membranectomy. In 14 patients aged over 60 years, internal peritoneal drainage of the hematoma by a low-pressure shunt system proved to be a reliable method of treatment with the following advantages: rapid neurological improvement; immediate mobilization; little stress for the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 15 publications
0
30
0
1
Order By: Relevance
“…The causes of treatment failure include the presence of nonliquefied hematomas with various bleeding foci 14) ; multilayer loculations within the hematoma, which produce noncommunicating compartments 22) ; and excessive formation of a solid membranes 5) . Occasionally, advanced age has been considered to be a risk factor for recurrence and reoperation 19,20) . However, most studies have demonstrated no relationship between recurrence rate and age 8,9,11,17,23) .…”
Section: Discussionmentioning
confidence: 99%
“…The causes of treatment failure include the presence of nonliquefied hematomas with various bleeding foci 14) ; multilayer loculations within the hematoma, which produce noncommunicating compartments 22) ; and excessive formation of a solid membranes 5) . Occasionally, advanced age has been considered to be a risk factor for recurrence and reoperation 19,20) . However, most studies have demonstrated no relationship between recurrence rate and age 8,9,11,17,23) .…”
Section: Discussionmentioning
confidence: 99%
“…10 Further studies also supported bilateral CSDH as a risk factor for recurrence (Figure 2). 18,19 It is though that patients with bilateral CSDH tend to have previous brain atrophy increasing the risks of recurrence as discussed earlier.…”
Section: 13mentioning
confidence: 99%
“…In our series the rates of superficial and deep infections were 1.05% and 0.5%, respectively. The rate of superficial infections ranged from 0.2% to 1.5% in literature (27,33,36,56,57), while the rate of deep infections varied from 0.7% to 5.5% (4,12,35,41,56,(58)(59)(60)(61)(62). Deep infections can be life-threatening as it was the case in our series.…”
Section: Discussionmentioning
confidence: 43%
“…It is noteworthy to mention that we did not observe complications associated with the drain. A review of the literature reported recurrence rates in 0% to 37% of patients (5,6,17,21,35,39,41,43,49,50,57,61,(70)(71)(72)(73)(74)(75). We observed 14.2% of recurrences; they were mainly observed in mixt and hyperdense lesions.…”
Section: Discussionmentioning
confidence: 54%